A self-assembled bisoxazoline/Pd composite microsphere as an excellent catalyst for Suzuki–Miyaura coupling reactions. Issue 4 (9th October 2015) - Wang, Junke; Zong, Yingxiao; Wang, Xicun; Hu, Yulai; Yue, Guoren; Pan, Yi
Abstract : A palladium complex based on a novel oxazoline, a solid microsphere catalyst, was successfully prepared. Abstract : A palladium complex based on a novel oxazoline, a solid microsphere catalyst, was successfully prepared. The structure and composition of the solid catalyst were characterized by SEM, 1 H NMR, TGA and FT-IR. This catalyst exhibits high catalytic activity for Suzuki–Miyaura cross-coupling reactions of various aryl halides and arylboronic acids in aqueous media. Moreover, the catalyst shows outstanding stability and reusability, and it can be recovered simply and effectively and reused eight times without any activity decrease.